Unveiling an unknown colony: (Revista de História Regional, 2024)
This paper analyses a sample of 121 photographs of the former Portuguese colony of Timor taken between the 1890s and the 1910s. Using a semiotic and photojournalistic methodology and combining in the analysis photographic images with textual sources (parliamentary debates, military reports, press reports and written opinion of experts on overseas issues), this study shows how photography represented Timor and how this representation was presented in the metropolis. The imagetic sample indicates an eminently ethnographic and anthropological interest on the part of Portuguese photographers, who wanted to make up for the poor knowledge of that colony of colonial decisionmakers in Lisbon. Still, there was an effort to promote Timor as a possible emigration destination through photographs that showed the domestication and Portugalisation of the territory or the agricultural and mineral potential of the colony. Thus, this paper contributes to historiographical debates on the use of photography as a primary source and the role of that technology in the imperial agendas of European nations in Africa and Asia.
Keywords: photography; imperialism; colonialism; representations